LEG MUSCLE QUALITIES AND CHANGE OF DIRECTION SPEED OF VOLLEYBALL PLAYERS - Poček, Sunčica; Vuković, Milenko (Scientific Journal Management in Sports, 2014)
Volleyball is an open skill sport with explosive – dynamic muscle actions, jumping ability and speed in executing rapid, multidirectional movements. Twenty one collegiate volleyball players, (age 19.85 +/- 0.83 years; height 181.67 +/- 12.03 cm; weight 72.62 +/- 12.99 kg; train- ing experience 6.76 +/- 2.21 years), were recruited for this study. The purpose of this study was to examine the relationship between leg muscle qualities and change of direction speed. The following tests were performed: Block jump, Spike jump, Standing broad jump, Jelka test, T – test, 93639 m test, and Dash 20 m. Pearson’s coefficient of correlation from package SPSS 15.0 was used for data processing. The results showed that vertical jump abilities, straight sprinting speed and change of direction speed are distinct physical qualities. Therefore, train- ing and testing these extremly important abilities for performance of volleyball players should be highly specific.